Study of Genetic Divergence in Barnyard millet (Echinochloa frumentacea (Roxb.) Link) Germplasm - Arya, Rinkey; Bhatt, Arun; Kumar, Vineet (International Journal of Bio-resource and Stress Management, 2018)
The present investigation was carried out for genetic divergence of barnyard millet (Echinochloa frumentacea (Roxb.) Link) germplasm during Kharif, 2014 at Research Block, Department of Crop Improvement and Seed Testing at Department of Seed Science and Technology, V. C. S. G. Uttarakhand University of Horticulture and Forestry, College of Forestry, Ranichauri (Uttarakhand) with 35 diverse genotypes as EC-134192, IC-543, EC-578, IEC-411, RAU-11, VL-222, IC-595, PRB-402, EC-756, RAU-2, VL-232, IEC-515, IC-542, IEC-111, TNAU-149, PRB-802, IEC-546, PRB-903, VL-174, IEC-523, PRB-401, IEC-566, IEC-513, PRB-904, VL-230, VL-239, TNAU-155, IEC-636, IEC-531, VL-182 and PRB-9402, of barnyard millet including three checks viz., VL-172, VL-207 and PRJ-1. In genetic divergence, all thirty-five genotypes were grouped by using Mahalanobis D² stastistic into 6 clusters irrespective of geographical diversity, indicating no parallelism between geographic and genetic diversity. The cluster pairs exhibiting very high inter-cluster distances were cluster IV and VI, cluster IV and V, cluster II and IV, cluster III and VI, cluster I and IV and cluster III and IV. Considering cluster mean and genetic distance the crossing between genotypes of clusters IV with genotypes of cluster VI and those genotypes of cluster V would be fruitful for obtaining transgrassive segregants for developing high yielding and better quality barnyard millet varieties.